L’assurance responsabilité découlant des produits - Hébert, Sylvie; Calandriello, Frank M. (Assurances)

(untitled) (HEC Montréal, 1990)
In this article, the authors, Sylvie Hébert and Frank M. Calandriello, explain Product Liability Insurance, covering some of the basic principles and technical aspects governing insuring agreements, exclusions and conditions, such as insurance coverage trigger, the definition of occurrence, the duty to defend and the duty of disclosure. A variety of forms have been used for Product Liability Insurance over the years, from product and completed operations coverage to product extorsion or product guarantee insurance. Here is the first part of the study. The second part will appear in our next issue.